2021
DOI: 10.3906/kim-2101-12
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antioxidant activities of new nickel(II) complexes derived from 4-benzy- loxysalicylidene-S-methyl/propyl thiosemicarbazones

Abstract: Six nickel(II) complexes of the N 2 O 2 chelating thiosemicarbazones were synthesized using N 1 -4-benzyloxysalicylidene-S-methyl/propyl thiosemicarbazone and methoxy-substitute-salicylaldehydes in the presence of Ni(II) ion by template reaction.The structures of thiosemicarbazones and nickel(II) complexes were characterized by elemental analysis, UV-Vis, IR and 1 H-NMR spectroscopies. The structure of the N 1 -4benzyloxysalicylidene-S-propyl thiosemicarbazone (2) was determined by X-ray singlecrystal diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Tese compounds which contain N and S atoms usually act as bidentate or multidentate chelating ligands and can coordinate to transition metal ions through the sulfur and hydrazine nitrogen atoms [1]. Extensive investigations conducted by researchers have demonstrated that metal complexes with some thiosemicarbazone derivatives present a wide range of biological applications, such as antibacterial [2,3], antifungal [1,4], antiparasitic [5], antitubercular [6,7], antiviral [8,9], antioxidant [10,11], and antitumoral activities [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Tese compounds which contain N and S atoms usually act as bidentate or multidentate chelating ligands and can coordinate to transition metal ions through the sulfur and hydrazine nitrogen atoms [1]. Extensive investigations conducted by researchers have demonstrated that metal complexes with some thiosemicarbazone derivatives present a wide range of biological applications, such as antibacterial [2,3], antifungal [1,4], antiparasitic [5], antitubercular [6,7], antiviral [8,9], antioxidant [10,11], and antitumoral activities [12][13][14].…”
Section: Introductionmentioning
confidence: 99%